PENGEMBANGAN KONTEN VIDEO PRODUK UKM SEBAGAI UPAYA PROMOSI MELALUI MEDIA SOSIAL - Muhammad Sholeh; Markus Andika; Muhammad Anwar fauzi; Bismin . (JURNAL GAUNG INFORMATIKA, 2021)
This study aims to develop the content for small and medium enterprises (SMEs) to be used for promotion on social media. Increasing the number of social media users, especially young people, can certainly be one of the promotion targets. Thus, the existence of social media must be utilized by SMEs to become one of the promotional media. The method used the qualitative method. The steps for developing media content are (1) pre-production, (2) production (3) postproduction, (4) Upload to social media (5) Evaluation of the content results. The results are video content of SME agents that can be used as a medium of promotion and uploaded on social media.